GREENLAND - FROM AUTONOMY TO (IN)DEPENDENCE - Brańka, Tomasz (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The purpose of this paper is to analyze the process of development of Greenland’s autonomy, especially vis-à-vis the Act on Greenland Self-Government of 2009, which ensures that decisions on the future status of the island will be made by the people of Greenland. Compared to other entities, Greenland is the only Arctic territory which can feasibly gain independence. This study also discusses the relations between Denmark and Greenland in terms of post-colonial relations between the former metropolis/colonizer and the island, outlining also the discourse on independence in Greenland. The hypothesis posed in the paper is that the proceeds from mineral extraction will not enable Greenland to become economically independent and abandon Danish subsidies, and that the process of gaining sovereignty might result in Greenland becoming dependent on external powers which will have a considerable impact on social relations on the island. This means that the matter under negotiation is not so much whether or not Greenland has the right to declare independence, but rather if it should take this step. Artykuł stawia sobie za cel analizę dotychczasowego procesu rozwoju autonomii terytorialnej Grenlandii, szczególnie w kontekście Aktu o Samorządzie z 2009 r., w którym uzgodniono, że decyzja o przyszłym statusie wyspy przynależeć będzie do narodu grenlandzkiego. W ujęciu porównawczym, Grenlandia pozostaje w regionie Arktyki jedynym autonomicznym terytorium, które ma możliwość uzyskania niepodległości. Praca podejmuje także temat relacji Danii z Grenlandią, w kontekście pokolonialnych stosunków między dawną metropolią a wyspą, zarysowując również dyskurs niepodległościowy na największej wyspie świata. Postawiona hipoteza zakłada, że dochody z przemysłu wydobywczego nie umożliwią szybkiego uniezależnienia się ekonomicznego wyspy i całkowitej rezygnacji z duńskiej subwencji, a proces dochodzenia do niepodległości będzie niósł ryzyko uzależnienia się od sił zewnętrznych, znacząco wpływając na stosunki społeczne na wyspie. W ...